Lung Cancer Screening Outreach Program in an Urban Native American Clinic - Camille Robichaux; Madison Anderson; Rebecca Freese; Antony Stately; Abbie Begnaud (SAGE Publishing, 2023)
Objectives: To evaluate uptake of lung cancer screening in an urban Native American clinic using 2 culturally targeted promotion strategies. Methods: Patients eligible for lung cancer screening from July 2019 to July 2021 were randomized to receive either a single culturally-targeted mailer from the clinic regarding possible eligibility for screening, or the same mailer plus a follow-up text message and additional mailing. Results: Overall, there were low rates of shared decision-making visit scheduling (8.5%) with no difference between promotion strategy groups (9.4% in control group vs 7.7% in culturally-targeted outreach group). Only about 50% of the lung cancer screening CT exams ordered were completed and returned to the clinic. Conclusions: While there was no difference between arms in this intervention, 8.5% of the sample did complete a shared decision-making visit after these low-cost interventions. The gap between the number of screening CTs ordered and number who completed the CT represents an area where further interventions should focus.